Reducing Postoperative Neurological Complications in Uniportal Full-Endoscopic Lumbar Interbody Fusion: Efficacy of the GUARD Technique Combined With Delayed Ligamentum Flavectomy - Hao-Chun Chuang; Yu-Chia Hsu; Yuan-Fu Liu; Chao-Jui Chang; Yu-Meng Hsiao; Yi-Hung Huang; Keng-Chang Liu; Chien-Min Chen; Hyeun Sung Kim; Cheng-Li Lin (Neurospine)
Objective Uniportal full-endoscopic transforaminal lumbar interbody fusion (FE-TLIF) carries a unique risk of nerve traction and abrasion injury during cage insertion. This study aims to evaluate the clinical efficacy of the GUARD technique and delayed ligamentum flavectomy in reducing postoperative radicular pain and neurapraxia in patients undergoing uniportal FE-TLIF. Methods A retrospective analysis was conducted on 45 patients with an average age of 53.9±12.4 years who underwent either FE facet-sparing TLIF (FE fs-TLIF) or FE facet-resecting TLIF (FE fr-TLIF). Patients were divided into 2 groups: the sentinel group (21 patients) using traditional sentinel pin techniques, and the GUARD group (24 patients) using the GUARD technique with delayed ligamentum flavectomy. Patient-reported outcomes included the visual analogue scale (VAS) for leg and back pain, and Oswestry Disability Index. Complication rates, including incidental durotomy, postoperative neurapraxia, and hematoma, were also documented. Results Postoperative radicular pain in the legs was significantly reduced at 6 weeks in the GUARD group compared to the sentinel group (VAS: 2.201 vs. 3.267, p=0.021). The incidence of postoperative neurapraxia was markedly lower in the GUARD group (0% vs. 19%, p=0.047). Both groups showed similar improvements in disc height, segmental lordosis, and lumbar lordosis at the 1-year follow-up, with no significant differences in endplate injury or fusion rates. Conclusion The GUARD technique and delayed ligamentum flavectomy significantly enhance patient safety by reducing postoperative radicular pain and neurapraxia without incurring additional costs. These techniques are easy to learn and integrate into existing surgical workflows, offering a valuable improvement for surgeons performing FE-TLIF procedures.